Right ventricular–pulmonary arterial coupling and its relationship to exercise haemodynamics in a continuum of patients with pulmonary vascular disease due to chronic thromboembolism. Issue 3 (22nd September 2022) - Douschan, Philipp; Tello, Khodr; Rieth, Andreas J.; Wiedenroth, Christoph B.; Sassmann, Teresa; Kovacs, Gabor; Ghofrani, Hossein A.; Seeger, Werner; Richter, Manuel; Guth, Stefan
Chronic thromboembolic pulmonary disease (CTED) and chronic thromboembolic pulmonary hypertension (CTEPH) represent a continuum of pulmonary vascular disease (PVD) characterised by chronic occlusion and remodelling of pulmonary arteries and arterioles after pulmonary embolism [1]. While CTEPH is defined as PVD with elevated mean pulmonary arterial pressure (mPAP) and pulmonary vascular resistance (PVR) at rest, patients with CTED show normal or only mildly elevated resting mPAP but may have significantly compromised pulmonary exercise haemodynamics. It has been previously shown that right ventricular (RV) function, assessed as the ratio of RV end-systolic elastance to pulmonary arterial (PA) elastance (Ees/Ea), may be affected in both CTED and CTEPH [2, 3]. Like pulmonary exercise haemodynamics, RV–PA coupling may already be impaired in the setting of preserved cardiac output (CO) and normal pulmonary haemodynamics at rest. The ratio of tricuspid annular plane systolic excursion (TAPSE) to systolic pulmonary arterial pressure (sPAP) has been recently established as a simple surrogate for RV–PA coupling [4]. We aimed to assess the association of TAPSE/sPAP ratio with clinical characteristics, including resting and exercise haemodynamics in patients with CTED and CTEPH. We hypothesised that assessment of RV–PA coupling may help to identify PVD and pathological pulmonary exercise haemodynamics. This retrospective study shows that TAPSE/sPAP ratio, a simple surrogate of RV–PA coupling, may help to identify patients with PVD due to chronic thromboembolism and predicts impaired pulmonary exercise haemodynamics https://bit.ly/3osXxzV